Understanding hospital length of stay in trauma laparotomy patients: a National Trauma Database Study - Jeremy Grushka; Kosar Khwaja; Hayaki Uchino; Evan G Wong (Trauma Surgery & Acute Care Open)
Introduction The diverse procedures and varying patient conditions in trauma laparotomy cases lead to significant variability in hospital length of stay (HLOS), posing challenges for effective patient care. Strategies to reduce HLOS are varied, with multiple factors potentially modifiable through targeted interventions. These interventions are most effective when target populations and their associated factors are clearly defined. This study aimed to stratify trauma laparotomy patients by their HLOS and identify factors associated with HLOS to enhance patient care.Methods A retrospective analysis was conducted using the National Trauma Data Bank from January 2017 to December 2019. Adult trauma patients who underwent trauma laparotomy following blunt or penetrating abdominal injuries were identified using International Classification of Diseases, 10th Revision codes and Abbreviated Injury Scales. HLOS was stratified into three groups based on the IQR of the study population: short (< 5 days), medium (5–11 days) and long (> 11 days).Results A total of 27 434 trauma laparotomy patients were identified. The overall median HLOS was 7.0 (5.0, 11.0) days. Penetrating mechanisms, particularly stab wounds, were strongly associated with a short HLOS. Additionally, isolated abdominal trauma, splenic injuries or spleen-related procedure were more likely to result in a short HLOS. Patients with a long HLOS experienced higher rates of in-hospital complications and were more frequently discharged to home with home health services or to extended care facilities. Most comorbidities were associated with a long HLOS, and patients with Medicaid or Medicare had a higher likelihood of a long HLOS.Conclusion Despite the relatively homogenous trauma population, HLOS distribution varied significantly. Stratification based on HLOS revealed distinct factors associated with short and long HLOS categories, indicating that targeted interventions for each category could potentially reduce HLOS and enhance patient outcomes in the current era of constrained healthcare resources.Level of evidence, study type Level IV, therapeutic/care management.